Senegal : Request for a Three-Year Policy Coordination Instrument-Press Release; Staff Report; and Statement by the Executive Director for Senegal. (IMF Staff Country Reports; Country Report, 2020)
Economic growth averaged 6.5 percent over the past five years, boosted by public investment under phase I of Senegal's development strategy, the 'Plan Senegal Emergent' (PSE), and buoyant private consumption. High public financing needs led to a rapid increase in public debt and a widening of the current account deficit. The outlook remains favorable provided Senegal strictly adheres to the WAEMU fiscal deficit target of 3 percent of GDP and creates fiscal space for investment through enhanced revenue mobilization and spending efficiency to stabilize public debt. Hydrocarbon production is projected to start in 2022. The authorities requested the cancellation of the 2015-19 Policy Support Instrument (PSI) in early 2019 (with only one review left), and are now requesting approval of a three-year program supported by the Policy Coordination Instrument (PCI) to underpin implementation of the second phase of the PSE.